An analysis of Shadow in Lord Henry Character in Oscar Wildeâ€™s â€œthe Picture of Dorian Grayâ€: The application of Carl G. Jungâ€™s Psychoanalysis - Winda Wulandari DJ (ELITE: Journal of English Language and Literature, 2018)
This study is aimed to analyze The Picture of Dorian Gray by Oscar Wilde in terms of analytical psychology. The problem concerns revealing the Shadow of Lord Henry's character which is portrayed in The Picture of Dorian Gray. The objective of this study is to analyze the shadow of Lord Henry's character in The Picture of Dorian Gray. This study used the descriptive qualitative method. The source of data in this study is a novel by Oscar Wilde, titled The Picture of Dorian Gray which is published in 1890. The data were collected through the process of previewing, reading, and annotating and then the writer analyzed those data by using the theory of psychoanalysis by Carl Gustav Jung. It is found that Lord Henry is dominated by his shadow, as he cannot balance the other archetypes in his personality. He cannot define his true self because his shadow keeps haunting him, or in other words, Lord Henry’s self is the Shadow. Lord Henry’s shadow is manifested into Envious, Hypocrisy, Fear, Misogyny, and Machiavellian which is portrayed in The Picture of Dorian Gray. The other archetypes also play important role in arousing Lord Henry’s shadow such as Persona and Anima. The worst thing about Lord Henry’s shadow that it is not only affecting himself but also affecting another character that is Dorian Gray, where it thrusts and motivates Lord Henry to give destructive influence over him and eventually awakes Dorian’s own shadow.